An Unhealthy Nutritional Transition: Consequences of the Decrease in the Apparent Consumption of Legumes in Chile, 1996-2018; [Una Transición Nutricional No Saludable: Consecuencias de la Disminución del Consumo Aparente de Legumbres en Chile, 1966-2018] - Rojas-Lobos, F (Centro de Estudios de Historia Agraria de America Latina, 2023)
The nutritional transition in Chile involved significant changes in diet between 1990 and 2000, in particular the rapid increase in the consumption of meat and dairy as principal sources of protein and calories. This article analyses another key trend: the reduction in apparent legume consumption between 1966 and 2018. The principal results indicate a decline in the apparent consumption per capita of beans, chickpeas and peas, while the consumption of lentils experienced a slight increase. In addition, it is established that the socioeconomic sectors that allocate a greater proportion of their income to legumes are those in the third quintile. The main impacts of these dietary changes on public health are explained and it is argued that the country experienced an unhealthy nutritional transition during this period. Finally, the article presents the potential benefits of a higher intake of vegetable protein from legumes in a possible new phase of nutritional transition. © 2023 Oles Honchar Dnipro National University. All rights reserved.